Greek Science in the Long Run : Essays on the Greek Scientific Tradition (4th c. BCE-17th c. CE). - Olmos, Paula (Cambridge Scholars Publishing, 2012)
Greek traditions relating to both the arts and sciences of life and health and those regarding the systematic development of theories of measurement and quantification enjoyed an incredibly long reputation and showed a kind of versatility that challenges any simplistic, dogmatic or a priori viewpoint about the meaning and social function of systematic knowledge. In this sense, they allow us to focus on very specific traits of the multiple processes of production, textual arrangement and trans ...